Demilitarisation Nigeria and South Africa compared - Isima, J (Department of Defence Management and Security Analysis, 2009)
In sub-Saharan African countries that have made democratic transition from military rule and military-backed authoritarian regimes, state elites have embarked upon strategies aimed at demilitarising the new democratic political process. Demilitarisation of the state and politics has become an imperative because it is decisive for consolidating democratic politics and for ensuring improvements in public safety and security. Yet the process of such demilitarisation in these countries has often generated a paradox, whereby the reduction of the political influence of state institutions of violence has been associatedw ith rising civil militarism and the prevalenceo f organised violence in the wider society. In these circumstances, taking cognisance of the dangers of civil militarism and other forms of private violence is a priority for designing and implementing demilitarisation strategies and other security reforms in post-authoritarian African states. Reformminded political elites and external supporters need to be sensitive to these dangers or risk perpetuating the shell of electoral democracy that cannot deliver the goal of human security in the region. This dissertation explored how the current approach to demilitarisation is related to the problem of civil militarism by examining the case studies of Nigeria and South Africa. It explains that given the condition of the state in Africa, demilitarisation of politics after transition from military or military-backed authoritarianism contributes to the emergence of civil militarism. Based on this finding, it argues for a comprehensive approach to demilitarisation as a strategy that caters to both state and societal violence in order to mitigate the risks of civil militarism in the process.
Keywords: Conflict management - Africa, Southern; Africa, Southern --Politics and government; International political economy of new regionalisms series